A comprehensive modular system of prevention of professional destructions of the investigators in the course of their professional formation - Kovalchishina, S. (Psihologiâ i pravo, 2017)
The article substantiates the need to improve the readiness of the future legal psychologists to effective coping behavior in the light output at the present time in Russia professional standards governing the activities of professionals providing psychological assistance to minors, including those who are in legally relevant situations. The aim of the presented research - the identification of typical coping strategies for students of legal psychology in the educational practice and the analysis of the relationship of coping strategies with successful performance practices. Second-year students were diagnostic practice in various educational institutions, including schools and special schools for students with deviant behavior. Probationers acted as a psychologist, a holistic diagnostic problem solving - from the receipt of the request to make recommendations on the results of the survey. The method of content analysis was processed 41 report on the practice. Fixed mention of problematic situations that have caused negative emotions in the trainees, and mention of coping behavior. Revealed the typical difficulties of students and coping strategies when performing queries on psycho-diagnostics of children with behavioral problems. We found a significant positive correlation between the success of the implementation of practice tasks students with a variety mentioned in the report difficulties with the frequency of their appearance, as well as with a variety of coping strategies. The study offers methodological tools for the preparation of the future legal psychologists in diagnostic practice. Статья посвящена вопросам профессионального развития личности, в частности профессиональной компетентности следователей в период их становления. Анализируются также вопросы профессиональной пригодности следователей к выполнению возложенных на них задач. Автором рассматриваются технологии формирования необходимых профессиональных качеств у следователей, акцентируется особое внимание на эффективности тренинговых методов обучения в рамках служебной подготовки сотрудников следственного управления. Предлагается комплексная модульная система предупреждения профессиональных деструкций следователей, которая ориентирована на развитие и саморазвитие профессионально важных качеств следователя и осознанное отношения к собственному профессиогенезу. В модульную систему включены четыре модуля: правовой, организационно-кадровый, образовательно-педагогический и психологический, которые позволяют эффективно воздействовать на профессиональное становление как действующих сотрудников следственных подразделений, так и будущих следователей. Предлагается разработанная и апробированная автором комплексная психопрофилактическая тренинговая программа «Психологическая поддержка следователя (ППС)», которая активно используется в настоящее время в рамках служебной подготовки следователей органов внутренних дел.